Management of Levies at Fish Auction Places in Increasing Regional Original Income in Cirebon Regency - Muhammad Nurhadi Hansyaekh (Social Impact Journal, 2022)
This paper is about the management of fish auction site fees in increasing the Cirebon district's original regional income and the criteria for success in managing the fish auction house fees in increasing the Cirebon district's original income. In this research is descriptive analysis that is using a qualitative approach that is directed to describe the facts and appropriate arguments. Based on the results of the research, it was said that the management of the levy at the fish auction place was good but not optimal, it can be seen from the acceptance of retribution every year for the last 5 years, which has increased in the last 3 years and decreased in the following 2 years due to the ongoing pandemic. However, the contribution of fees for fish auctions in increasing local revenue in Cirebon district tends to be unstable. As for the procedures for managing fees for fish auctions, the success criteria that affect the management of fees for fish auctions in increasing local revenue.